Determinación del consumo horario residencial de agua potable de las parroquias San Andrés y San Isidro pertenecientes al cantón Guano - Carrión Tenesaca, Juan Carlos (2023)
The rural parishes of San Andrés and San Isidro de Patulú, belonging to the Guano canton which are located in the northwest of the province of Chimborazo. It covers 51.87 % of the cantonal area. Each parish has a distribution network called the Lalanshi network (San Andrés) and Chancaguán network (San Isidro de Patulú). The purpose of this research project is to determine the residential hourly consumption of drinking water and its relationship with socioeconomic strata. Based on the methodology of urban stratification and socioeconomic survey proposed by Arellano et al. (2012), through the data collected from 96 micrometers in San Andrés and 64 micrometers in San Isidro de Patulú for 24 hours, 7 days a week; the habits that influence water consumption were established. As well as the variation curves of hourly consumption and the maximum and minimum coefficients of variation of hourly consumption (kh). Obtaining that the highest consumption of drinking water in the San Andrés parish take place at 12:00 with a flow of 126.72 l/h and in San Isidro de Patulú at 11:00 with a flow of 103.22 l/h. In turn, the coefficients (kh) of greatest magnitude are 2.44 and 3.08 respectively, which exceed the limit maximum of 2.30 suggested in the CPE INEN 5 standard (1992) for use in the design of distribution networks, because there are no studies that determine a (kh) in the study areas.